Complete genome characterization by nanopore sequencing of rotaviruses A, B, and C circulating on large-scale pig farms in Russia - Nikita Krasnikov; Alexey Gulyukin; Taras Aliper; Anton Yuzhakov (Virology Journal)
Abstract Background Rotaviruses are the major etiological agents of gastroenteritis and diarrheal outbreaks in plenty of mammalian species. The genus Rotavirus is highly diverse and currently comprises nine genetically distinct species, and four of them (A, B, C, and H) are common for humans and pigs. There is a strong necessity to comprehend phylogenetic relationships among rotaviruses from different host species to assess interspecies transmission, specifically between humans and livestock. To reveal the genetic origin of rotaviruses from Russian pig farms, nanopore-based metagenomic sequencing was performed on the PCR-positive specimens. Methods Samples were selected among the cases submitted to routine diagnostic or monitoring studies to the Laboratory of Biochemistry and Molecular Biology of “Federal Scientific Center VIEV” (Moscow, Russia). The selected positive samples were genotyped using nanopore sequencing method. Results Five porcine RVA isolates were completely sequenced, and genotype analysis revealed various porcine G/P genogroups: G2, G3, G4, G5, G11 and P[6], P[7], P[13], P[23], P[27] with a typical backbone constellation I5-R1-C1-M1-A8-N1-T1/7-E1-H1. The RVB isolate was detected in combination with RVA in a rectal swab from a diseased pig in Krasnoyarsk Krai. It was characterized by the following genogroups: G15-P[X]-I11-R4-C4-M4-A8-N10-T4-E4-H7. The first complete porcine RVC genome from Russia was obtained with genomic constellation G6-P[5]-I14-R1-C1-M1-A7-N9-T6-E1-H1, and the phylogenetic analysis revealed putative novel genotype group for the VP6 gene-I14. Additionally, the first porcine kobuvirus isolate from Russia was phylogenetically characterized. Conclusions The applied nanopore sequencing method successfully genotyped the RV isolates and additionally revealed co-circulated species. The study demonstrates high genetic variability of Russian RVA isolates in VP4/VP7 genes and phylogenetically describes local RVB and RVC. Complete characterization of genomic segments is a crucial methodology in tracing the rotavirus's evolution and evaluating interspecies transmissions.